1994
DOI: 10.1007/bf00144465
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide production by Aureobasidium pullulans: factors affecting polysaccharide formation

Abstract: Aureobasidium pullulans NRRL 6220 synthesized polysaccharide most actively in media containing sucrose, fructose or maltose with (NH4)2SO4 (0.6 g/l) or ammonium acetate giving greatest yields of the polysaccharide. With (NH4)2SO4 at ≥1.2 g/l, production of polysaccharide was decreased considerably. Polysaccharide production was highest with an initial pH of 6.5 while biomass formation was better below an initial pH of 5.5. Optimum phosphate concentration for polysaccharide production was 0.03 M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In previous studies, A. pullulans strain NRRL 6220 gave a higher EPS yield (32.7 g l -1 ) on (NH 4 ) 2 SO 4 than on other nitrogen substrates including ammonium citrate, NaNO 3 , and urea [1]. On the other hand, A. pullulans strain ATCC 42023 has given greater pullulan yields on complex nitrogen sources including peptone than that on ammonium sulfate [17].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, A. pullulans strain NRRL 6220 gave a higher EPS yield (32.7 g l -1 ) on (NH 4 ) 2 SO 4 than on other nitrogen substrates including ammonium citrate, NaNO 3 , and urea [1]. On the other hand, A. pullulans strain ATCC 42023 has given greater pullulan yields on complex nitrogen sources including peptone than that on ammonium sulfate [17].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the pullulan-producing strains of A. pullulans prefer ammonium as the sole nitrogen source for their EPS production, whereas that of the aubasidan-producing strains is nitrate 6,8,9 . Hence the effect of nitrogen source on the EPS production by NRRL 58539, NRRL 58543 and NRRL 58560 was investigated using Production Medium as previously described 3 .…”
Section: Methodsmentioning
confidence: 99%
“…After removal of the residual ethanol, the precipitate was dissolved in 3 ml of deionized water at 80 o C and the solution was dialyzed against deionized water for 48h to remove small molecules in the solution. The exopolysaccharide was precipitated again by using 6 ml of the cold ethanol and the residual ethanol was removed, the precipitate was then dried at 80 o C to a constant weight (Badr-Eldin et al, 1994). Pullulan weight was measured using electronic balance (Sartorius Limited, U.S.A.) and expressed in gram/liter.…”
Section: Isolation and Purification Of Extracellular Polysaccharidementioning
confidence: 99%